Maltrato infantil y actitudes hacia el aprendizaje en niños de la Institución Educativa Inicial N° 767 Comunidad 9 de octubre, San Pablo 2023 - Aricari Ríos, Juana Rosa (2024)
This study aimed to explore the relationship between child maltreatment and attitudes towards learning among children at the Initial Educational Institution No. 767, October 9 Community, San Pablo, in 2023. Methodology: A relational research type was adopted with a non-experimental, bivariate, cross-sectional, and field design. The study population consisted of 70 children, and data collection was carried out using two observation guides, both validated by experts and applied through direct observation. Results: Statistical analysis identified a significant negative correlation between child maltreatment and attitudes towards learning, evidenced by a Pearson correlation coefficient of -0.759. This finding indicates that a decrease in child maltreatment is associated with improvements in children's attitudes towards learning. This pattern was also supported by the scatter plot analysis. Conclusion: The research validates the existence of a significant negative relationship between child maltreatment and attitudes towards learning. These results emphasize the need to implement interventions that reduce child maltreatment to enhance positive attitudes towards learning in children.